Production of chicken sausage (Cobb 500 (Smith, 1992)): caracterisation of Physicochemical, microbiological and sensorial qualities.: Qualities of chicken sausage produced in Cameroon (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of this work is to produce chicken sausage, hence, increasing the added value of chicken. The physicochemical and sensorial qualities were evaluated. Microbial quality was investigated during a period of one month under vacuum storage conditions at 4°C. From the results, it appears that the physicochemical parameters of chicken meat before processing and chicken sausage showed a significant (p<0.05) difference. The chicken sausage compared to the chicken meat, presents good physicochemical characteristics (an acidic pH of about 5.1, a lowered water content of 67.33 ± 0.76 % to 60.00 ± 0.87% and a relatively high water retention capacity from 28.85 ± 1.46% to 69.24 ± 0.52%) for its better preservation. The microbiological quality of chicken sausage was studied over a period of four weeks under one storage condition (4°C) and showed that the chicken sausage is fairly safe for consumers compared to the recommended levels (absence of salmonella, a total mesophilic aerobic flora of 2.6.103 ± 3.8.102 CFU/g of product, a rate of Staphylococcus aureus, Escherichia coli respectively 2.05.101±3.2 and 6.8±3.2 CFU/g of product) after four weeks chilling storage. The chicken garlic sausage was the best sample appreciated by consumers organoleptically with a percentage of 77.02%. Therefore, processing of chickens in chicken sausage can be a technological center to explore.